Hubungan perilaku hand washing dengan kejadian diare pada anak usia sekolah di sd negeri awan kintamani: Relationship of hand washing behavior with diarrhent events in school ages in sd negeri awan kintamani - resiyanthi, ni komang ayu; Ardiyanti, Ni Komang Pande; Faidah, Nurul (Bali Medika Jurnal, 2021)
School age is an important age in growth and development, in children of school age infectious diseases often occur such as diarrhea. Diarrhea can be transmitted through unclean hands and germs that enter the body when the hands touch the eyes, nose, mouth. Hand washing is the most important basic technique in preventing transmission of infection. This study aims to determine the relationship of hand washing behavior with the incidence of diarrhea in school-age children at SD Negeri Awan Kintamani. This research is a analytic correlation research with cross sectional approach. The population used in this study were students in grades IV, V, VI who were students SD Negeri Awan with a sample of 50 people with stratified random sampling technique. Data analysis using Chi Square statistical test. The results of hand washing behavior research in school-age children at SD Negeri Awan in the good category 72%, enough 22%, and the less category 6%. Whereas in children who have never experienced diarrhea 56%, and those who have experienced diarrhea 44%. The relationship of hand washing behavior with the occurrence of diarrhea obtained p-value = 0,000 that is smaller than 0.05 and contingency coefficient value = 0.534, then there is a relationship between hand washing behavior with the incidence of diarrhea in school-age children at SD Negeri Awan Kintamani. It is recommended that students be able to apply clean and healthy living behaviors by always disciplining handwashing practices to avoid the risk of diarrhea